A Graphene‐Based Bimorph Structure for Design of High Performance Photoactuators. (26th October 2015) - Hu, Ying; Wu, Guan; Lan, Tian; Zhao, Jingjing; Liu, Yang; Chen, Wei
Abstract : A photoactuator based on a tubular‐shaped graphene composite bimorph is fabricated and shows reversible photoactuation with fast response and large deformation (deformation angle of ca. 479° in only 3.6 s), which is mostly attributed to the interfacial thermal stress. Various photoactuator devices based on the tubular bimorph, including a smart box and crawler‐type robot that can mimic tank‐track motion, are designed.